Profile of PEGylated interferon beta in the treatment of relapsing-remitting multiple sclerosis - Cocco E; Marrosu MG (Dove Medical Press, 2015)
Eleonora Cocco, Maria Giovanna Marrosu Multiple Sclerosis Center, Department of Public Health, Clinical and Molecular Medicine, University of Cagliari, Cagliari, Italy Abstract: Several treatments are currently available for relapsing-remitting multiple sclerosis. Among them, interferon (IFN) beta remains a valid treatment approach because of its good benefit/risk profile. Due to the need for frequent administration (weekly, at a minimum), the use of IFN beta is limited by uncomfortable side effects that could reduce adherence to and persistence with the treatment. The use of subcutaneous polyethylene glycol (PEG)ylated interferon beta-1a (PEG-IFN) has been proposed to offer a better combination of pharmacokinetic and pharmacodynamic profiles and therapy-related side effects. A 125 µg dose of PEG-IFN given every 2 or 4 weeks was tested in two Phase I studies and shown to be as safe and efficient as IFN beta-1a but with a longer half-life. A Phase III trial (ADVANCE) comparing 125 µg of PEG-IFN given every 2 or 4 weeks with placebo in 1,512 patients with relapsing-remitting multiple sclerosis showed significant reductions in both the annualized relapse rate (ARR) and the occurrence of new or newly enlarged T2 brain lesions in both experimental groups versus placebo after the first year. Moreover, 38% fewer patients showed progression of disability (P=0.04) in the PEG-IFN groups. During the second year, the ARR was further reduced in the PEG-IFN 2-week treatment group (0.230 at 1 year versus 0.178 at 2 years) and was maintained in the 4-week treatment group. Patients who received immediate PEG-IFN treatment showed improved clinical efficacy (ARR, risk of relapse, 12-week disability progression) and magnetic resonance imaging parameters (new T2 and newly enlarging lesions, gadolinium-positive lesions) compared with those with delayed treatment. The effects were more evident with the 2-week dose for all endpoints considered. Furthermore, PEG-IFN was well tolerated, and no new safety concerns arose. In conclusion, PEG-IFN has good efficacy and a good safety profile. The available data support the use of PEG-IFN as a suitable therapeutic option in patients with relapsing-remitting multiple sclerosis. Keywords: PEGylated interferon beta, multiple sclerosis, disease-modifying drug, relapses, magnetic resonance imaging, safety